Pengaruh metode penyarian terhadap kadar alkaloid total daun jembirit (Tabernaemontana sphaerocarpa. BL) dengan metode spektrofotometri visibel - Salamah, M.Sc, Apt., Nina; Rozak, Miftahul; Al Abror, Muhti (Pharmaciana, 2017)
One of the plants which contain the alkaloid is a plant jembirit (Tabernaemontana sphaerocarpa BL. ).Sap and leaves from this plants have been used to treat skin diseases and sprain. Alkaloid from jembirit plants showed potent cytotoxicity against various human cancer cell. The goal of this research is to find out the influence of the extraction method against the level of total alkaloid jembirit leaves.Jembirit leaves were extracted by maceration method and extraction with Soxhlet apparatus used ethanol 70 % as a solvent . Standardization of extracts conducted by test of ash content, test of drying shrinkage, and extract yield. Qualitative analysis conducted by alkaloid test. Determination of total alkaloid was analyzed with visible spectrophotometry method using Bromocresol green as complexing agent. The results showed that jembirit leaves contained alkaloid compounds. The determination resulted the levels of total alkaloid of maceration was 0.727% ± 0.0032, levels of total alkaloid extraction with Soxhlet apparatus was 0.666% ± 0.0022. The stastitical analysis showed significance differences of total alkaloid levels between maceration method and extraction with Soxhlet apparatus viewed from siginificancy value (0.001<0.005).